Ventricular arrhythmia susceptibility in a new porcine model of heart failure (HF) with reduced ejection fraction. (14th October 2021) - Melka, J; Helbert, A; Lesage, L; Moreau, K; Romariz, K; Berson, P; Isabelle, M; Delerive, P; Tyl, B
Abstract: Introduction: Sudden death secondary to ventricular arrhythmias is common in HF patients, with no effective treatment available outside of implantable cardiac defibrillators. While animal models are essential for the discovery of anti-arrhythmic drugs, no reliable large animal HF models with associated ventricular arrhythmias have been described so far. Objectives: We aimed at evaluating ventricular remodeling and arrhythmia susceptibility in an HF pig model with reduced ejection fraction (EF) following myocardial infarction (MI). Methods: MI was induced in 53 male Göttingen minipigs (12–15 months, 20–25 kg) by coronary embolization in mid-left anterior descending and mid-left circumflex coronary arteries using endovascular coils. Seven other pigs underwent sham operation and were used as control. Two weeks after surgery, cardiac function was assessed by echocardiography, and animals were included based on EF<50% (n=15/53), assigned either to 12 weeks of vehicle (n=9) or perindopril (n=6, 1 mg/kg/d, per os) group. At the end of the study, their left ventricular (LV) electrical remodeling was studied by echocardiography/electrocardiography and a programmed-electrical stimulation protocol was performed to evaluate the susceptibility to develop ventricular arrhythmias. Results: At the end of the study, animals in the vehicle group had a significant LV remodeling associated with a reduced EF (p<0.05 vs. sham, see table). This remodeling was associated with cardio-pulmonary congestion, significant increases in LV end-diastolic pressure, left atrial volume, and lung mass (all p<0.05 vs. sham, see table), fully prevented by perindopril treatment. They had also an electrical remodeling as evidenced by an increase in PR, QRS, and QTc intervals, as well as LV effective refractory period (+18%, 14%, 33%, and 13%, respectively, p<0.05, compared to sham animals). Electrical changes were mitigated by perindopril treatment (p=NS vs. sham). LV mechanical dispersion measured with speckle-tracking echocardiography was significantly increased in vehicle group (58±5 vs. 22±1 ms in sham group, respectively) as well as in perindopril group. Programmed-electrical stimulations induced in 6/8 vehicle animals either non-sustained (n=3) or sustained (n=2) ventricular tachycardia, or ventricular fibrillation (n=1). In sham group only 1/7 animal had a ventricular fibrillation. No inducible ventricular arrhythmia was observed in animals treated with Perindopril. Conclusion: In this new pig model of congestive HF with reduced EF, LV remodeling was associated with electrical remodeling and susceptibility to develop arrhythmias. Chronic angiotensin-converting enzyme inhibitor treatment prevented congestion, mitigated electrical remodeling, and suppressed arrhythmia susceptibility. FUNDunding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Servier Research Institute - CardioVascular & Metabolic Diseases Center for Therapeutic Innovation